Bee colonies in melon crop yield, Santa Elena province - Suárez Ricardo, Elvis Antonio; Quito León, Erik Patricio; Valarezo Quinaluisa, Rodrigo Andrés (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2022)
Context: The research was carried out in the Prosperidad commune belonging to the Santa Elena canton in Ecuador. Two demonstration plots were used, in one a Langstroth model mobile bee hive was implanted and the other without bees, with the aim of evaluating the incidence of bees in the melon crop to increase its yields. Method: A completely randomized design (DCA) with two treatments and five repetitions with a total of 10 experimental units was implemented, in which fertilized flowers, formed fruits, aborted fruits, crop productivity and agricultural yield were evaluated. An analysis of variance was performed on the collected data and those that showed significant differences were applied Tukey's multiple comparison test at 0.5%. Results: The addition of the bee hive to the cultivation tasks shows better agronomic variables, in fertilized flowers and formed fruits, also the largest number of aborted fruits. The best average yield of the melon crop is observed in the treatment pollinated with bees. Productivity was higher in the treatment used by bees, allowing a more uniform fruit set. Conclusions: The use of bee hives in melon cultivation is recommended.
Keywords: Bees; Hives; Melon; Pollination